What Did the Lady Forget? - Ozu, Yasujiro; Atsuta, Yûshun; Shigehara, Hideo; Kurishima, Sumiko; Saito, Tatsuo; Kuwano, Michiko (BFI, 2010)
Tradition and modernity, freethinking and emotional inhibition form the lines of conflict in Yasujiro Ozu’s 1937 melodrama, centered on Komiya, a nearly middle-aged Tokyo doctor and medical professor, and his wife, Tokiko, who welcome Setsuko, her nearly grown niece from Osaka, as a houseguest. Tokiko dresses and lives according to Japanese custom; Setsuko wears American-style clothing and enjoys the freedoms of Western manners - smoking, drinking, driving, and indiscreetly displaying her interest in the doctor’s most promising medical student. But Tokiko imposes her traditional ways on the rationalist Komiya as well; she bluntly dictates his schedule and sharply interrogates him about his activities, and Setsuko, seeing him squirm, prods him to revolt. The plot pivots on Komiya’s lie to his wife about playing golf when in fact he visits a geisha house - and meets Setsuko there. Ozu catches quietly violent feelings in images of a seemingly improvisational spontaneity, and he imbues the action with an exquisitely understated eroticism. But the story also involves physical violence, and Ozu discerns a strange and disturbing tangle of mixed emotions beneath established formalities; his view of progress is bitterly ironic. [www.newyorker.com]
Keywords: DVD-Video